Regional Externalities - Heijman, Wim (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Wim Heijman Wageningen University, The Netherlands, E-mail: wim. heijman@wur. nl Generally speaking, externalities occur when a decision causes uncomp- sated costs or benefits to individuals or groups other than the person(s) making the decision. Examples of negative externalities are numerous in the area of the environment and natural resources. Some negative extern- ities result because a particular type of manufacturing technology is used (e. g. water and air pollution caused by industry). Other negative extern- ities occur because of the transportation system (e. g. air pollution caused by intensive car traffic). Though positive externalities draw less attention than negative externalities, their existence is obvious, for example, b- keepers who provide unpaid pollination services for nearby fruit growers or the positive network effects of a telephone system. The more people who own a telephone, the more useful the device is for each owner (Boardman et al. , 2001). From a social planner's perspective, the existence of externalities - sults in an economic process outcome that is not socially optimal because marginal costs of the product involved do not equal its price. This implies that, in a well functioning market economy, negative externalities cause too much of a product to be produced, whereas positive externalities cause too little of a product to be produced.